Effectiveness of home-based pulmonary rehabilitation: systematic review and meta-analysis. (21st September 2022) - Uzzaman, Md. Nazim; Agarwal, Dhiraj; Chan, Soo Chin; Patrick Engkasan, Julia; Habib, G.M. Monsur; Hanafi, Nik Sherina; Jackson, Tracy; Jebaraj, Paul; Khoo, Ee Ming; Mirza, Fatim Tahirah; Pinnock, Hilary; Shunmugam, Ranita Hisham; et al.
Introduction: Despite proven effectiveness for people with chronic respiratory diseases, practical barriers to attending centre-based pulmonary rehabilitation (centre-PR) limit accessibility. We aimed to review the clinical effectiveness, components and completion rates of home-based pulmonary rehabilitation (home-PR) compared to centre-PR or usual care. Methods and analysis: Using Cochrane methodology, we searched (January 1990 to August 2021) six electronic databases using a PICOS (population, intervention, comparison, outcome, study type) search strategy, assessed Cochrane risk of bias, performed meta-analysis and narrative synthesis to answer our objectives and used the Grading of Recommendations, Assessment, Development and Evaluations framework to rate certainty of evidence. Results: We identified 16 studies (1800 COPD patients; 11 countries). The effects of home-PR on exercise capacity and/or health-related quality of life (HRQoL) were compared to either centre-PR (n=7) or usual care (n=8); one study used both comparators. Compared to usual care, home-PR significantly improved exercise capacity (standardised mean difference (SMD) 0.88, 95% CI 0.32–1.44; p=0.002) and HRQoL (SMD −0.62, 95% CI −0.88–−0.36; p<0.001). Compared to centre-PR, home-PR showed no significant difference in exercise capacity (SMD −0.10, 95% CI −0.25–0.05; p=0.21) or HRQoL (SMD 0.01, 95% CI −0.15–0.17; p=0.87). Conclusion: Home-PR is as effective as centre-PR in improving functional exercise capacity and quality of life compared to usual care, and is an option to enable access to pulmonary rehabilitation. Home-based pulmonary rehabilitation is as effective as centre-based in improving exercise capacity and quality of life, and is an option for people with COPD whose access to pulmonary rehabilitation centres is difficult .https://bit.ly/39HkMm4